2017
DOI: 10.1021/acs.jpcc.7b01607
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Photoexcitations and Trap-Assisted Recombination in TQ1:PC71BM Blends

Abstract: The generation and recombination of long-lived photoexcitations is clarified in TQ1 films and TQ1:PC 71 BM 1:1 and 1:3, by weight, blends using photoinduced absorption measurements. At 80 K triplets are formed in TQ1 films, while both triplets and polarons are formed in the 1:1 and 1:3 blends. We suggest that the triplet state acts as a loss mechanism for generation of free charges in these blends and suggest an energy diagram for the photoexcitations in the blends. We estimate the triplet polaron annihilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The t e for the devices with TQ1 and P3TI were very similari nt he same voltage region between0 .45 and 0.55 V. An increaseo f t e at lower light intensity was observed, which is expected when the concentration of photo-induced charges in the film decreases. TQ1 exhibits polarona bsorption at approximately 950 nm, [46,47] whicha greesw itht he new peak observed in the PIA spectrum of the device with TQ1 in Figure 7. Therefore, it is difficult to directly comparet he t e of the device based on P3HT with the other devices,ast he measurements were not performed at the same voltage.…”
Section: Resultsmentioning
confidence: 83%
“…The t e for the devices with TQ1 and P3TI were very similari nt he same voltage region between0 .45 and 0.55 V. An increaseo f t e at lower light intensity was observed, which is expected when the concentration of photo-induced charges in the film decreases. TQ1 exhibits polarona bsorption at approximately 950 nm, [46,47] whicha greesw itht he new peak observed in the PIA spectrum of the device with TQ1 in Figure 7. Therefore, it is difficult to directly comparet he t e of the device based on P3HT with the other devices,ast he measurements were not performed at the same voltage.…”
Section: Resultsmentioning
confidence: 83%
“…Triplet states are long-lived in the blend and can accumulate to densities of around half the free charge carrier density under short circuit conditions, their density only limited by triplet–triplet annihilation. The high triplet densities coupled with very low charge recombination losses indicate that triplet states do not necessarily reduce the performance of organic solar cells, in contrast to previous conclusions. , We stress that triplet formation is a very common feature in OPV blends, and that given their possibly large equilibrium density, it seems important to consider their impact on performance. The approach presented here is fairly universal and enhances our understanding of the role of triplet states in increasing or reducing carrier recombination losses.…”
mentioning
confidence: 55%
“…8 Moreover, studies by Gehrig et al demonstrated that when triplets are formed on the polymer, they are a reservoir of excitations, that, to a certain extent, can replenish the charge carrier population via triplet-triplet annihilation in PBDTTC-C:PC61BM blends. 18 For the present study, we chose blends of the donor polymer TQ1 and fullerene derivative PC71BM, since they exhibit clear triplet formation, 27 yet they also exhibit high internal quantum efficiencies in devices. [28][29][30][31] We observed, quantified, and parametrized both charge and triplet state formation and decay, which in turn enabled us, not only to simulate charge densities in operating devices, but also to calculate the corresponding triplet densities by solving the triplet rate equation under steady-state conditions.…”
Section: Toc Graphicmentioning
confidence: 99%
See 1 more Smart Citation
“…The defects in the active layer bring rise to new energy states within the band gap called electronic traps . These traps are potential sites for recombination to occur and hence the defect density in the material has to be minimized …”
Section: New Design Principles In Biophotovoltaicsmentioning
confidence: 99%